IMPROVING LEARNING OUTCOMES IN WRITING POETRY THROUGH THE CONTEXTUAL TEACHING AND LEARNING (CTL) - Rozala, David; Jonas, Meet (Edelweiss : Journal Of Innovation In Educational Research, 2025)
The purpose of this research is to improve the learning outcomes of writing poetry through the Contextual Teaching And Learning (CTL) learning approach in fourth grade students of SD Negeri 1 Maluku Tengah. The subjects of this research were 24 fourth grade students , consisting of 10 male students and 14 female students. This research uses a Classroom Action Research design with a qualitative approach. The procedures/steps of classroom action research are: (1) determining the focus of the research problem, (2) implementing the cycle, (3) analyzing data, (4) planning follow-up, (5) ending the action. The instruments used in this research include: (1) tests, (2) observation sheets. The results of the poetry writing skills test for students in cycle II were classified as High, namely there were 21 students who completed (88%) and 3 students who did not complete (12%). This condition increased from the condition of cycle I where there were 12 students who completed (50%) and 12 students who did not complete (50%). Likewise, in the pre-cycle condition, only 3 students (12.5%) completed the task, and the remaining 21 students (87.5%) did not. Based on the data obtained in the pre-cycle condition, the condition in cycle I, and the condition in cycle II, it can be concluded that learning to write poetry using the Contextual Teaching and Learning approach in cycle II was successful. This can be seen from the results of observations of student learning activities in cycle II, which have reached the predetermined criteria. The percentage of student activity in cycle II was 82.3%. Therefore, the average score obtained by students in writing poetry successfully reached the minimum completion criteria (KKM) determined by the school. In addition, at least 75% of the total number of fourth-grade students obtained scores according to the KKM. (completed).